A repeated imitation model with dependence between stages: Decision strategies and rewards - Villacorta, Pablo J.; Pelta, David A. (Zielona Góra: Uniwersytet Zielonogórski)
Adversarial decision making is aimed at determining strategies to anticipate the behavior of an opponent trying to learn from our actions. One defense is to make decisions intended to confuse the opponent, although our rewards can be diminished. This idea has already been captured in an adversarial model introduced in a previous work, in which two agents separately issue responses to an unknown sequence of external inputs.
Keywords: adversarial decision making; imitation; strategies; state dependence; rewards